Sodium dodecyl benzene sulfonate-catalyzed reaction for aromatic aldehydes with 1-phenyl-3-methyl-5-pyrazolone in aqueous media - Yongjun Zheng; Yong Zheng; Zhen Wang; Yana Cao; Qian Shao; Zhanhu Guo (Green Chemistry Letters and Reviews, 2018)
Sodium dodecyl benzene sulfonate was successfully used for the tandem Knoevenagel-Michael reaction of aromatic aldehydes with 1-phenyl-3-methyl-5-pyrazolone in water to synthesis of 4, 4′-arkylmethylene-bis(1-phenyl-3-methyl-5-pyrazolones) under mild reaction conditions. Efficient catalytic activity and high selectivity of the catalyst contributed to colloidal particle formation in water. The shape and size of the colloidal aggregates were confirmed by optical microscopy and dynamic light scattering.